Key management in open DRM platforms - Serrão, C.; Dias, M.; Delgado, J. (Third International Conference on Automated Production of Cross Media Content for Multi-Channel Distribution (AXMEDIS'07), 2007)
Key management is the set of techniques and procedures supporting the establishment and maintenance of keying relationships between authorized parties. DRM platforms are usually composed by a set of different functionalities and components that usually manage and exchange keying material in a secure way. This key material has to be properly and securely managed in order to avoid the security compromise of these DRM platforms. Unfortunately, most of the DRM platforms don't have this concern in mind and disregard an appropriate key management life cycle. In this paper, we will analyze some of the open-specification and/or open-source DRM platforms, focusing this analysis on the open DRM platforms key management life cycle, and how this life cycle is implemented on each of them. The results will be presented in a comparative way.